PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN VIDEO ANIMASI TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V DI SDS PELITA KASIH SINGKAWANG - Levy Tampubolon, Smohoker; Fitriyadi, Slamat; Setya Novanto , Yogi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to: 1) determine the implementation of the Problem Based Learning model assisted by animated videos on the critical thinking skills of fifth grade students at Pelita Kasih Elementary School, Singkawang, 2) determine whether there is an effect of the application of the Problem Based Learning model assisted by animated videos on the critical thinking skills of fifth grade students at Pelita Kasih Elementary School, Singkawang, 3) determine how much influence the application of the Problem Based Learning model assisted by animated videos on the critical thinking skills of fifth grade students at Pelita Kasih Elementary School, Singkawang. The type of research used is quantitative research with an experimental method. The research design used is a one group pretest-posttest design. The population in this study were all fifth grade students at Pelita Kasih Elementary School, Singkawang, with a sample of 22 students taken using the total sampling technique. The prerequisite test used was the Shapiro-Wilk normality test. The results of the normality test showed that the pretest significance value was 0.213 and the posttest significance value was 0.318, both of which were greater than 0.05, indicating a normal distribution. Hypothesis testing used a paired sample t-test. The results showed that the average pretest score was 29.45 and the average posttest score was 76.27, with a mean difference of 46.82. The t-test results obtained a calculated t-value of 18.631 with a significance value (Sig. 2-tailed) of 0.000 <0.05, so the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Furthermore, the effect size test results obtained a Cohen's d value of 3.972, which is in the very high category.